2000
DOI: 10.1074/jbc.m001327200
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Estrogen Receptor Interaction with a Repressor of Estrogen Receptor Activity (REA) and the Regulation of Estrogen Receptor Transcriptional Activity by REA

Abstract: The transcriptional activity of nuclear hormone receptors is known to be modulated by coregulator proteins. We found that the repressor of estrogen receptor activity (REA), a protein recruited to the hormone-occupied estrogen receptor (ER), decreased the transcriptional activity of ER, both when ER was acting directly through DNA response elements as well as when it was tethered to other transcription factors. Administration of antisense REA resulted in a 2-4-fold increase in ER transactivation, implying that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
115
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(123 citation statements)
references
References 44 publications
7
115
0
1
Order By: Relevance
“…Prohibitin was found complcxed %vith either Rb or E2FI in diHerent cell types including Ramos cells without overexpression of any component, as detected by immunofS^uf o"~^"*^™ '''°t experiments (Wane et al, 1999a,b) Because the Rb binding domain and the E2F binding domain on prohibitin are distinct (amino acids /4-I16 versus 184-214. respectively), the three P'"°*^'"s could potentially associate together at the Oncogene same time. Our results on a transcriptional regulatory role for prohibitin are further supported by the studies showing that a highly related protein, Phb2/BAP37/ REA mediates the repression of estrogen receptors (Delage-Mourroux et al, 2000; Collectively, these observations suggest that while prohibitin might have other functions in the cell (Nijtmans et al, , 2002 its mitochondrial functions, if any, are distinct from' its ability to bring about transcriptional repression or powth suppression.…”
Section: Discussionsupporting
confidence: 73%
“…Prohibitin was found complcxed %vith either Rb or E2FI in diHerent cell types including Ramos cells without overexpression of any component, as detected by immunofS^uf o"~^"*^™ '''°t experiments (Wane et al, 1999a,b) Because the Rb binding domain and the E2F binding domain on prohibitin are distinct (amino acids /4-I16 versus 184-214. respectively), the three P'"°*^'"s could potentially associate together at the Oncogene same time. Our results on a transcriptional regulatory role for prohibitin are further supported by the studies showing that a highly related protein, Phb2/BAP37/ REA mediates the repression of estrogen receptors (Delage-Mourroux et al, 2000; Collectively, these observations suggest that while prohibitin might have other functions in the cell (Nijtmans et al, , 2002 its mitochondrial functions, if any, are distinct from' its ability to bring about transcriptional repression or powth suppression.…”
Section: Discussionsupporting
confidence: 73%
“…Furthermore, in other cell types, PHB2 has also been suggested to be localized in the nucleus and modulate transcriptional activity by interacting with transcription factors, including nuclear receptors, either directly or indirectly 12,[29][30][31][32] . PHB2 has been shown to interact with and inhibit the transcriptional activity of the ER in breast cancer 12 .…”
Section: Discussionmentioning
confidence: 99%
“…However, a growing body of evidence indicates that this model is too simple and not adequate to explain the dynamic pattern of transcriptional regulation [20]. It has previously been shown that liganded ERa is able to interact with a selective repressor protein illustrating an unpredictable mode of action for liganded receptors [21]. On the other hand, in a recent report, the activator function of apo-ERa was also demonstrated [7].…”
Section: Ectopic Era Expression In Mda-mb-231 Upregulates Nis Expressionmentioning
confidence: 99%